Compact multilayer equal size printed rectangular antenna - Subahir, Suhaila; Esa, Mazlina; Yusof, Sharifah Kamilah; Fisal, Norsheila; Murad, Noor Asniza (2001)
Mierostrip antennas are printed circuits operating In the microwave range. They are based on the low cost technology and thus shoUld be potentially suited for low cost consumers. This paper presents the design of a multiJayer rectangular microstrip patch antenna operating at three different frequencies. The frequencies choosen are 1.227 GHz and 1.575 GHz for Global Positioning System (GPS) satellite receiver and 2.45 GHz for Wireless Local Area Network (LAN) application. The size of the patch element is determined mathematically using the mathematical software Mathcad 2000. Numerical simulations were carried out using Micropatch v.2 electromagnetic software.